Real-time advanced sensorless control of axial flux synchronous motor - Hassan, Amir Yassin; Ebrahim, Essamudin Ali; Salem, Saber Mohamed Saleh; Elzalik, Mohamed (Institute of Advanced Engineering and Science, 2024)
Interior rotor axial flux permanent magnet synchronous motor (IRAFSM) sensorless control is essential to inject the motor inside the electric vehicles’ tire. The proposed straight-line guided by the reference speed (SLGBRS) sensorless space vector pulse width modulation (SVPWM) inverter-direct torque control (DTC) technique for driving the IRAFSM used for electric vehicles (EVs) is evaluated using laboratory emulator setup. A hardware-in-the-loop (HIL) controller and data acquisition are used as a real-time emulation, while the results are compared with MATLAB simulation results. Both simulation and real-time application of the proposed sensorless control for the IRAFSM offer a good speed response. The results of real-time evaluation are identical with the simulation results so, the control is accurate and suitable for practical applications. Urban dynamometer driving cycle (UDDS) for heavy-duty vehicles is used as a driving cycle for simulation and real time evaluation. UDDS is used to ensure the reliability of the proposed control against a wide range of speed changes to be applicable for many applications. The proposed technique allows utilizing the IRAFSM in many applications that requires less contact and reduced sensors like robotics and inside EV’s tire with a good reliable control.